Assessing the toll of COVID-19 lockdown measures on the South African economy - Arndt, Channing; Gabriel, Sherwin; Robinson, Sherman (International Food Policy Research Institute, 2020)
In trying to limit the spread of COVID-19, policymakers are confronting the difficult task of balancing the positive health effects of lockdowns against their economic costs — particularly the burdens imposed on low-income and food-insecure households. South African lockdown policies are relatively stringent, and the economic impacts are large. Figure 1 presents impacts on the income components of gross domestic product (GDP), based on an analysis using a social accounting matrix (SAM) model, a tool well-suited to assessing the impacts of shortterm shocks. The work is a collaboration between IFPRI, the National Treasury of South Africa, the South African Reserve Bank, and UNU-WIDER.